ОСНОВНЫЕ НАПРАВЛЕНИЯ РАЗВИТИЯ НАУКИ В СООТВЕТСТВИИ С ПРОГРАММНЫМИ СТАТЬЯМИ ПРЕЗИДЕНТА КАЗАХСТАНА Н.А. НАЗАРБАЕВА - Исмаилов, С.С.; Бисембаева, А.К. (My University, 2019)
Аннотация В данной статье рассматривается вопрос об основных направлениях исторической науки в связи с программными статьями Президента Казахстана Н.А. Назарбаева. Авторы отмечают, что концептуальные программные документы, озвученные главой государства, всегда отличаются новым видением исторического прошлого нашей страны. Подобные про- граммные статьи актуализируют известные исторические факты, но сказанные на высоком государственном уровне. Такое отношение позволяет говорить о модернизации общества и его исторического сознания. Abstract This article discusses the main directions of historical science in connection with the program articles of the President of Kazakhstan N.A. Nazarbayev. The authors note that the conceptual program documents voiced by the head of state are always distinguished by a new vision of the historical past of our country. Such program articles actualize the known historical facts, but said at a high state level. This attitude allows us to talk about the modernization of society and its historical consciousness.
The main directions of development of science in accordance with the program articles of the President of Kazakhstan N.A. Nazarbayev
Keywords: Президент; история; модернизация; общественное сознание; программная статья; President; history; modernization; public consciousness; program article